The Hindenburg : the fiery crash of a German airship - Deady, Kathleen W. (Minnesota : Capstone High-Interest Books, 2003)
Describes the giant airship "Hindenburg," the events that led up to its explosive crash on a New Jersey airfield in 1937, and the effects of the disaster on airship travel.
Includes bibliographical references and index.
Keywords: Hindenburg (Airship) -- Juvenile literature; Hindenburg (Airship); Aircraft accidents -- New Jersey -- Juvenile literature; Airships -- Germany -- Juvenile literature; Airships; Aircraft accidents